2019
DOI: 10.3389/fmicb.2019.01684
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Import of a Secreted “Candidatus Liberibacter asiaticus” Protein is Temperature Dependent and Contributes to Pathogenicity in Nicotiana benthamiana

Abstract: “ Candidatus Liberibacter asiaticus” (CLas), one of the causal agents of citrus Huanglongbing (HLB), secretes proteins with functions that are largely unknown. In this study, we demonstrated that CLIBASIA_00460, one of the CLas-encoded Sec-dependent presecretory proteins, might contribute to the phytopathogenicity of CLas. CLIBASIA_00460 was conserved in CLas strains and expressed at a significantly higher level in citrus than in Asian citrus psyllid. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 49 publications
5
69
0
1
Order By: Relevance
“…Based on the genomic information of CaLas, several reports focused on the virulence mechanisms of CaLas [7][8][9][10]. The identified effectors could cause cell death of infiltrated leaves [6,8], systemic leaves necrosis [7], and inhibition of plant growth [8]. Mature proteins of CLIBASIA_03915 (m03915) and CLIBASIA_04250 (m04250) caused phloem necrosis in the senescent leaves of N. benthamiana when expressed by TMV ( Figure 2) and functioned at the protein level (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the genomic information of CaLas, several reports focused on the virulence mechanisms of CaLas [7][8][9][10]. The identified effectors could cause cell death of infiltrated leaves [6,8], systemic leaves necrosis [7], and inhibition of plant growth [8]. Mature proteins of CLIBASIA_03915 (m03915) and CLIBASIA_04250 (m04250) caused phloem necrosis in the senescent leaves of N. benthamiana when expressed by TMV ( Figure 2) and functioned at the protein level (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The effectors of CaLas mainly rely on Sec secretion machinery to enter host cells. Several reports have used transient expression or viral vectors to identify the effectors of CaLas [6][7][8]. CaL5315 was reported as a lethal effector, causing cell death in infiltrated N. benthamiana leaves by transient expression [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because HLB is a major threat to the citrus industry [1], numerous research studies have been conducted, including studies on the identification of the causal agent [3,61], the cellular structure change of the infected trees [27,62], confirmation of the causal agent from putative-infected trees [5,9,10,12,63], and detection of the putative-infected trees [6,8,13,14]. In spite of the studies that were done to understand the pathogenesis of Ca Las [30,32,33,34,64] and the gene regulation of Ca Las [65], the virulence mechanism is still largely unknown, because of the unavailability of the mutant library. The accessibility of genomic information of Candidatus Liberibacter [4,35,66,67] makes screening the putative virulence factors possible by expression candidates in planta.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogen has not been cultured, and the virulence mechanisms of C Las remain largely unknown. Nevertheless, several reports have shown that C Las encodes effectors to inhibit citrus plant defense and development [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%